Why teach? - Parsons, Aaron (Childhood education, 2003)
Parsons discusses several factors why people choose the education profession. Most people go into education for the sheer amount of monetary rewards, some people enjoy a certain subject area, others look to help work towards a better tomorrow, and others enjoy working with children.